Pengembangan Aplikasi Komputer Pengolah Data Konsentrasi Obat Dalam Plasma Untuk Studi Pemodelan Parameter Farmakokinetik - A, Sukmadjaja; S, Lucy; Q, Muhammad (UI Scholars Hub, 2006)
A computer application named Farmakomatic 1.0 had been developed to calculate pharmacokinetic parameters from plasma drug concentration data following intravenous and oral administration with one and two compartment model using a program application Microsoft® Visual Basic 6.0®. The application was evaluated using two plasma drug concentration data. Calculation results of the Farmakomatic 1.0 and manual calculation using Microsoft® Excel 2003® were not different.